Ministry of Investment and International Cooperation The General Authority for Investment And Free Zones Decree No. 39 of the Year 2019 Promulgating The Regulations of Free Zones Management System = قرار رئيس الهيئة العامة للاستثمار والمناطق الحرة رقم 39 لسنة 2019 بإصدار لائحة نظام لائحة إدارة نظام إدارة المناطق الحرة - Egypt; The middle east library for economic services, translator. (2025)
Chapter - 1: General provisions Chapter - 2: Procedures of licensing the establishment of free zones projects 9. Chapter - 3: Executive, import and export procedures 14 Chapter - 4: Organizational and financial procedures Chapter- 5: Procedures for the liquidation of projects and companies, waiver thereof and administrative 25 evacuation